Reception of the Pentateuch in the Medieval Polish Apocrypha of the New Testament - Rojszczak-Robińska, Dorota (Verbum Vitae, 2023)
The purpose of this article is to analyze the translation and reception of the Pentateuch in medieval Poland by examining the Old Polish (vernacular) apocrypha of the New Testament. It analyses, for example, passages in which a verse from the Pentateuch is quoted or paraphrased, in which a quotation from the Books of Moses is omitted by an evangelist, as well as all passages in which the names of various figures and heroes of the Old Testament Pentateuch, are invoked. It turned out that in medieval Polish-language biblical apocryphal narratives the Pentateuch functions differently from other biblical and patristic sources. It is not used as freely as the Gospels or the Psalms. It is used to characterize the Jewish world and the precepts of the Law. Quotes from the books of Moses rarely function as prophecies. The Pentateuch in Old Polish apocrypha functions as a reservoir of stories, a collection of catchphrases to be evoked. This is because while the heroes of the Old Testament were prominent in preaching, art, and language, the text of the Torah was not frequently translated into the Polish language.